Evaluation of arterial stiffness between peritoneal dialysis and hemodialysis in patients with renal replacement therapy - Günay, Tufan; Topal, Dursun; Akgür, Suat (The European Research Journal, 2023)
Objectives: The aortic stiffness index beta (ASI-β), calculated noninvasively with the pressure change caused by arterial strain and volume changes on echocardiography, shows a strong correlation with invasive measurements of arterial stiffness. This study aimed to compare arterial stiffness and distensibility between peritoneal dialysis (PD) and hemodialysis (HD) and patients in renal replacement therapy. Methods: This cross-sectional and observational study analyzed 108 patients under renal replacement therapy (PD and HD). The aortic stiffness index beta (ASI-β) was calculated for each group. Results: The mean age of the patients in the study was 58.2±11.1 years, and 49 (45.4%) of the patients were female and 59 (54.6%) were male. Age, gender, comorbid rates, and levels of blood pressure and heart rate did not differ between the PD and HD groups. Blood pressure levels and heart rate. Mean aortic strain (5.6±1.9 vs. 9.4±2.8, p < 0.001) and median distensibility (1.5 vs. 2.9 cm, p < 0.001) were lower in the PD group than the HD group, while median ASI-β (11.6 vs. 6.2, p < 0.001) and mean E/e’ (10.6±2.9 vs. 9.2±2.3, p = 0.006) were higher in the PD group. The rate of concentric hypertrophy was higher in the PD group (47.5% vs. 23.5%, p = 0.005). Conclusion: PD patients have higher arterial stiffness and lower distensibility levels compared to HD patients. Therefore, patients with PD may be more prone to diastolic dysfunction, cardiovascular disease, and events.